PENGARUH KEPEMILIKAN MANAJERIAL, DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT, DAN KONSERVATISME AKUNTANSI TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
The purpose of this research is to analyze the effect of managerial ownership, the independent board of commissioner, audit committee, and accounting conservatism on earnings management of manufacturing companies that listed on Indonesia Stock Exchange. The research was perfomed because of the global phenomenon of accounting scandal and the inconsistency of former researches. Agency theory was used as the grand theory of this research. The data for this research was collected from Indonesia Stock Exchange website (www.idx.co.id) and the purposive sampling method was used to filter the data population. The final sample used for this research was 27 manufacturing companies from all sectors of manufacturing industry within 2011 - 2013 and obtained 81 observation data as the final data input to be tested through this research.The result of the research concludes that both managerial ownership and the independent board of commissioner have negative and no significant effect on earnings management, while both audit committee and accounting conservatism have negative and significant effect on earnings management.